To Act or Not to Act: Endocannabinoid/Dopamine Interactions in Decision-Making - Hernandez, Giovanni; Cheer, Joseph F. (Frontiers in Behavioral Neuroscience, 2015)
Decision-making is an ethologically adaptive construct and multiple psychiatric disorders display impairments in this cognitive process. Activity within the mesocorticolimbic dopamine system has been traditionally associated with decision-making. The endocannabinoid system through its actions on inhibitory and excitatory synapses modulates dopamine activity and decision-making. The aim of this brief review is to present a synopsis of available data obtained when the endocannabinoid system is manipulated and dopamine activity recorded. To this end, we review research using different behavioral paradigms to provide further insight into how this ubiquitous signaling system biases dopamine-related behaviors to regulate decision-making.